Development of digital and science, technology, engineering, and mathematics skills in chemistry teacher training - Elías, Michal; Pérez, Javiera; Cassot, Montserrat del Rosario; Carrasco, Eduardo Andrés; Tomljenovic, Marijana; Zúñiga, Elisa Ariadne (Frontiers in Education, 2022)
Citizens of the twenty-first century use specific skills to solve real-life problem situations, propose interdisciplinary solutions, and sustainably solve their communities’ socio-scientific and technological problems, locally and globally. Science, technology, engineering, and mathematics (STEM) education is an integrated and interdisciplinary teaching-learning space. STEM careers are subject to gender gaps in terms of access to higher education, and only a quarter of female students follow a STEM career. Moreover, later in their professional careers, women often obtain lower salaries and income in the STEM professions. STEM education seeks to actively engage students by incorporating technologies into teaching-learning processes since, favoring searching, analysis, solution, and simulation of socio-scientific problems. The latter has become highly visible during the pandemic caused by COVID-19, particularly in emergency remote education measures. Information and communication technologies (ICT) plays a role in online education, either via the knowledge involved in school curricula or an understanding of how the pandemic has evolved. This is a triple task for professors since they must have the right skills to train citizens of the twenty-first century, build new stimulating learning spaces for their highly technologized students, and develop these skills in their students. This article reviews the concepts associated with digital and STEM skills by analyzing a case study, exploring the perception of students in terms of their development of these competencies, and the commitments required in the study plans made by a Professor of Chemistry in a Chilean state university. A mixed investigation was undertaken, considering three phases with different methodologies. The first phase consisted of a bibliographic study, comparing both the digital and STEM skills of several organizations in Chilean education (UNESCO, MINEDUC, and ISTE). ISTE was used as the basis of the applied questionnaire to establish coherence in the dimensions coming from different reference frames. A second phase refers to the analysis of the study plan programs associated with STEM, ICT, and chemistry teaching, through an Analysis Matrix of Aprioristic Categories. In a third phase, the development of digital skills in undergraduate Chemistry students and professors were evaluated through the Digital Competence Questionnaire of Higher Education Students. Based on UNESCO information, the STEM competencies address both the content and its application to problems related to STEM careers in a manner consistent with the training model for science and chemistry teachers. In the case of digital skills, UNESCO integrates international reference frameworks respecting each country’s laws, enabling them to adapt them. In Chile, MINEDUC focuses on teachers’ use of digital tools to improve the teaching-learning processes of students; and ISTE is focused on the skills of higher education. The analysis of the study programs shows that students’ digital skills do not meet the requirements of the Chilean Ministry of Education (MINEDUC). However, the programs enhance more complex cognitive levels when the curricula advance, promoting STEM skills. The digital competence questionnaire for higher education students (CDAES) survey showed a development proportional to the curricular pursuit of the students where, in the first year of the degree, the students declare positive answers in 60.5% of the items consulted. This trend increases in the second and third years (90.7% of positive answers) and the fourth and fifth years (93.0 and 95.4% of positive answers). It remains a challenge to develop skills to design, create or modify technological educational media that promote the use of digital and STEM skills. In conclusion, this research proposes digital and STEM skills for teacher training, discussing the relevance of their integration in STEM teaching and learning. The teacher training curriculum does not have an explicit association with digital and STEM skills, although it addresses the skills required by national and international benchmarks. However, the students indicate positive attitudes toward the digital skills developed progressively during their training as teachers. As future Chemistry teachers, they value the development of digital teaching skills that allow them to address the challenges that arise in the classroom and thus promote the appreciation of STEM careers, which helps form citizens with more sustainable intentions.